Sediment carbon storage of mangrove forest at Sungai Tinggi, Perak - Mat Din, Muhamad Huzwa (2016)
Sediment have a potential in storing carbon gases from the atmosphere and plays an important role in carbon cycle at mangrove ecosystem. In mangrove ecosystem sediments were found abundancely in the river brink. Therefore, to prove this statement, the study of carbon storage in the sediment was carried out at Sungai Tinggi in Matang Mangrove Forest, Perak. The objectives of this study are to provide a fundamental information of sediment carbon stored and to compare the carbon storage potential among three different zones and five different depths. One transet line was established along the river and divided into three zones (Upstream, Middle stream, Downstream). A total of 75 sediment samples were collected using peat auger in five different depths (0-15 cm, 15-30 cm, 30-50 cm, 50-100 cm, >100 cm). The standard method was used in sediment preparation and laboratory analysis. The obtained data was analyzed using SAS 9.2 to find mean comparison between zones and depths. As a result, middle stream with 10.819a (±0.234) % was obtained the highest content of total organic carbon compare to the other zones and shows significant different. In term of sediment depth, total organic carbon percentage was highest in depth five (>100 cm) with 12.528a (±0.281) %. As a conclusion, sediment is one of the potential for carbons stored but more research are need to be done to prove that the total organic carbon percentage are encourage by mangrove zones and depths.